Glass Ceiling Sebagai Hambatan Dalam Mewujudkan Keadilan dan Kesetaraan Gender Bagi Perempuan Pekerja - Azwar Azwar (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This paper discusses the phenomena of the glass ceiling, which affects women's chances of obtaining professional jobs, as well as its connection to issues of equality and equity in regards to gender. A literature review of several scientific studies that address the glass ceiling is used as the method of writing for this method. The findings of this literature review indicate that the "glass ceiling" phenomenon is still a barrier for women to overcome in order to advance to particular levels within their respective workplaces. The sexist attitude toward women was one of the contributing factors to this result. This article demonstrates that equality and equity in terms of gender have not yet been achieved in the field of professional labor.Keyword: Glass Ceiling, Equity, Equality.  AbstrakTulisan ini membahas tentang fenomena glass ceiling yang mempengaruhi peluang perempuan memperoleh pekerjaan profesional, serta kaitannya dengan isu kesetaraan dan kesetaraan gender. Tinjauan pustaka dari beberapa kajian ilmiah yang membahas mengenai glass ceiling digunakan sebagai metode penulisan untuk metode ini. Temuan kajian literatur ini menunjukkan bahwa fenomena “glass ceiling” masih menjadi kendala yang harus dihadapi perempuan untuk naik ke level tertentu di tempat kerjanya masing-masing. Sikap seksis terhadap perempuan menjadi salah satu faktor yang berkontribusi terhadap hasil ini. Pasal ini menunjukkan bahwa kesetaraan dan pemerataan gender belum tercapai di bidang ketenagakerjaan profesional.Kata kunci: Glass Ceiling, Kesetaraan Gender, Keadilan Gender